Exploring Film Marketing Dynamics : Analysis of Blockbusters and Independent Films' Marketing Impact on Audience Engagement. - Bagewadi, Prasanna; Machek, Martin; Kolouchová, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The thesis examines the interplay and relationship between film marketing campaign strategies and audience engagement, and fills a gap in the literature, which typically ignores engagement as a meaningful and tangible outcome. This qualitative study analyses three film campaigns: Avengers: Endgame (2019), Deadpool (2016), and Host (2020), while also incorporating information from eight expert interviews in the film marketing industry. The analysis demonstrates how different scales of budgets influence the strategies that each film marketing campaign undertakes. Avengers: Endgame used secrecy, nostalgia and franchise loyalty; Deadpool used humour, virality and character-based content; and Host used cultural relevance and low-budget authenticity. The expert interviews also helped the research to demonstrate that engagement today signifies way more than it ever did. Engagement can now mean an emotional response, fan interaction or ongoing digital participation instead of mere ticket sales. The study utilises AIDA, Uses and Gratifications, and Opinion Leader Theory frameworks to give context to audiences’ actions. The findings show that audiences want authenticity, emotional connection, and relevance in a timely context. This thesis also provides useful insights to marketers on exploring how to create emotionally driven audience-focused campaigns in a rapidly evolving media landscape.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses